Road Accident Data Collection Systems in Developing and Developed Countries: A Review - Rabbani, Muhammad Babar Ali; Musarat, Muhammad Ali; Alaloul, Wesam Salah; Ayub, Saba; Bukhari, Hamna; Altaf, Muhammad (International Journal of Integrated Engineering, 2022)
The road accidents trigger major financial loss and casualties to the individual as well as the state as a whole. The intelligent safety systems are developed to provide all road users with a safe transport system. This approach acknowledges the sensitivity of individuals to extreme injury in road accidents and recognizes the need for the system for improvement. To establish a proper system for road accident prevention, records from prior accidents play a key role in the evaluation and prediction of the accident, damage, and consequences. Therefore, this study was performed to evaluate and comparing existing practices in developing and developed countries for collecting road accident data. Moreover, the manual and digital approaches of data collection are highlighted. Keeping this in mind, this review provides an overview of how developing countries currently collect their data and their data dissemination methods to extract such useful information, which could prove beneficial in deciding the road safety programs for the well-being of end-users.